KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM PEMBANGUNAN BUDAYA RELIGIUS DI SEKOLAH - Akhmad Hudaya; Abdul Rosyid; Suklani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article aims to analyze the role of the principal's transformational leadership in developing a religious culture in schools. Transformational leadership is viewed as an effective leadership model for creating positive change through role modeling, inspirational motivation, empowerment, and personal attention. This research employed a qualitative approach with a case study method, conducted at Lemahabang 01 Public Elementary School, Tanjung District, Brebes Regency. Subjects included the principal, teachers, students, and the school committee. Data were collected through in-depth interviews, participant observation, and documentation studies. Data analysis was conducted using the Miles & Huberman model, which encompasses data reduction, data presentation, conclusion drawing, and verification. The results indicate that the principal successfully implemented transformational leadership in strengthening a religious culture through four main dimensions: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. Various strategies were implemented to build a religious culture, including integrating Islamic values ​​into the school's vision and programs, promoting religious activities, empowering teachers, creating a religious environment, and collaborating with parents and the community. Supporting factors for implementation include stakeholder commitment, religious facilities, and external collaboration, while barriers include time constraints, differences in religious backgrounds, and external cultural influences. The study concluded that transformational leadership is relevant to Islamic leadership principles such as uswah hasanah (good character), syura (shariah), amanah (trustworthiness), and tarbiyah (educational guidance), and is effective in creating schools with an Islamic character and religious culture.